KONFLIK BATIN TOKOH UTAMA NOVEL AYAHKU(BUKAN PEMBOHONG) KARYA TERE-LIYE - Jeharu, Maria Sulastri (Humanis; Volume 5. No. 2. November 2013, 2014)
The object of this research is Tere- Liye’s novel Ayahku (Bukan) Pembohong, ( My Dad is (not) a liar). This novel has prominent psychological description of main character who meets with emotional conflict continuously. The content of this novel describes the feeling of regret of character Dam who hates his father tale. It is very interesting that this novel was chosen to be analyzed using personality theory. This novel is analyzed firstly in terms of relation structure of character, plot, and setting elements. The second is analysis of main character’s psychological description which includes id, ego ,and superego. The third is the description of emotional conflict of main character in relation with ego element. The main character in this felt threatened because of anxiety of subconscious nature which is in contrast with ratio. It arouses various psychological behaviors and inner conflicts. The results of this analysis describes the inner conflict between father and son was caused by fair tale. This novel mandate to readers in order to become an independent an spritied roomy the thorax.
Keywords: personality, conflict, psychological